Thrombus Composition in Cerebral Venous Thrombosis - Ghil Schwarz; Angelo Cascio Rizzo; Martina Di Como; Amedeo Cervo; Antonio Macera; Guglielmo Carlo Pero; Maria Costanza Aquilano; Beatrice dell’Acqua; Marco Bacigaluppi; Francesco Ruggieri; Arturo Chieregato; Emanuela Bonoldi; et al. (Stroke Research and Treatment)
Conclusion: Our exploratory study first shows that CVT thrombi are larger than AIS thrombi, with higher RBC content and lower fibrin, matching CT density. These findings enhance the understanding of CVT pathophysiology but need validation.